PENERAPAN KEBIJAKAN UNDANG-UNDANG ITE DALAM MENANGANI KEJAHATAN SIBER PENIPUAN ONLINE - Witarti Rabawati, Dwityas; Rica De Araujo, Rojalia; Zigha Nanga, Antonia Alfiayu; Recon Dopo Due, Ferdinandus Mario; Albertus Papu, Fransiskus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Cybercrime is a term that refers to a criminal activity that uses a computer or computer network as a means of acting and as a target or location to commit criminal acts. The Electronic Information and Transaction Law (UU ITE) No. 11 of 2008, which was then amended first by Law No. 19 of 2016 and the second amendment to Law (UU) Number 1 of 2024 which is the main legal basis in handling cybercrime in Indonesia. One of the cases of cybercrime in Indonesia is online fraud. The method in this research uses library research, which is a method with data collection by understanding and studying theories from various literature. The Electronic Information and Transaction Law (UU ITE) in Indonesia is a significant step in providing a clear legal framework to regulate interactions in cyberspace and deal with cybercrime. Although the ITE Law has undergone several revisions to adapt to technological developments and the needs of society, challenges in its implementation are still present, such as the potential criminalization of Internet users and uncertainty in the interpretation of some articles. The ITE Law regulates various types of cybercrime, including online fraud and the dissemination of harmful information, with the aim of protecting the public from the negative impact of information technology